Promising new catalytic properties of a Co (II)‐carboxamide complex and its derived Co3O4 nanoparticles for the Mizoroki‐Heck and the Epoxidation reactions. (8th July 2020) - Kiani, Mahsa; Bagherzadeh, Mojtaba; Meghdadi, Soraia; Fadaei‐Tirani, Farzaneh; Babaie, Maryam; Schenk‐Joß, Kurt
Abstract : The new Co(II) ‐ carboxamide complex (1 ) and Co3 O4 nanoparticles (2 ), by way of thermal decomposition of (1 ) have been efficiently synthesised in the environment‐friendly. X‐ray diffraction reveals a slightly distorted octahedral coordination of cobalt (four nitrogens and two oxygens) in (1 ) and regular octahedral or tetrahedral ones (oxygens only) in (2 ). The investigation of (1 ) and (2 ) in the Mizoroki‐Heck and epoxidation of alkens reactions showed them both to be powerful, green and inexpensive catalysts. Abstract : The new Co(II)‐ carboxamide complex(1) and Co3 O4 nanoparticles (2 ), by way of thermal decomposition of (1 ) have been efficiently synthesised in the environment‐friendly. X‐ray diffraction reveals a slightly distorted octahedral coordination of cobalt (four nitrogens and two oxygens) in (1 ) and regular octahedral or tetrahedral ones (oxygens only) in (2 ). The investigation of (1 ) and (2 ) in the Mizoroki‐Heck and epoxidation of alkens reactions showed them both to be powerful, green and inexpensive catalysts.